Gαi3-Dependent Inhibition of JNK Activity on Intracellular Membranes - Bastin, Guillaume; Yang, Jin Ye; Heximer, Scott P. (Frontiers in Bioengineering and Biotechnology, 2015)
Heterotrimeric G-protein signalling has been shown to modulate a wide variety of intracellular signalling pathways including the mitogen-activated protein kinase (MAPK) family. The activity of one MAPK family class, c-Jun N-terminal kinases (JNKs) have been traditionally linked to the activation of G-protein coupled receptors (GPCRs) at the plasma membrane. Using a unique set of G-protein signalling tools developed in our laboratory, we show that subcellular domain-specific JNK activity is inhibited by the activation of Gαi3, the Gαi isoform found predominantly within intracellular membranes such as the endoplasmic reticulum (ER)-Golgi interface, and their associated vesicle pools. Regulators of intracellular Gαi3, including Activator of G Protein Signalling3 (AGS3) and the regulator of G-protein signalling protein 4 (RGS4), have a marked impact on the regulation of JNK activity. Together, these data support the existence of unique intracellular signalling complexes that control JNK activity deep within the cell. This work highlights some of the cellular pathways that are regulated by these intracellular complexes and identifies potential strategies for their regulation in mammalian cells.